2011
DOI: 10.1007/s00405-011-1615-x
|View full text |Cite
|
Sign up to set email alerts
|

A national series of 244 sinonasal cancers in Finland in 1990–2004

Abstract: Sinonasal cancer is still a somewhat controversial entity because most series are single-center studies. The aim of this study was to give more accurate and generalisable information about treatment of the neck and prognosis of sinonasal cancer. Retrospective, population-based, multicentre study. Altogether 244 patients diagnosed in 1990-2004 were evaluated. The 3- and 5-year disease-specific survival (DSS) rates after treatment with curative intent were 68 and 57%, respectively. Regional status at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 17 publications
5
27
1
2
Order By: Relevance
“…As we found in our study, the predominance of men was obvious in previous works (10,11). The majority of neoplasms occurred in the fifth decade of life which are in support with findings in previous studies (2,3).…”
Section: Discussionsupporting
confidence: 85%
“…As we found in our study, the predominance of men was obvious in previous works (10,11). The majority of neoplasms occurred in the fifth decade of life which are in support with findings in previous studies (2,3).…”
Section: Discussionsupporting
confidence: 85%
“…consider that "rhinomaxillary syndrome" is pathognomonic of lepromatous leprosy only when the full spectrum of lesions is present, but this is not the case of either skeleton 3 or 6. Even if this were the case the pathognomonic value of this syndrome is not consensual because this anatomical region may be involved in many other disease processes such as mucocutaneous leishmaniasis (Herwaldt, 1999;Manchester, 1994;Aufderheide and Rodríguez-Martín, 1998;Ortner, 2003;Malekpour and Esfandbod, 2010;Marsteller et al, 2011), neoplasms (Hackett, 1976;Aufderheide and Rodríguez-Martín, 1998;Ortner, 2003;Eggesbø, 2012;Koivunen et al, 2012), rhinoscleroma (Becker et al, 1981;Pontual et al, 2008), rhinosporidiosis (Bonifaz et al, 2011), sarcoidosis (Manchester, 1994;Mrówka-Kata et al, 2010), systemic mycosis (Zargari and Elpern, 2009;Bonifaz et al, 2011), treponematosis (Hackett, 1976;Manchester, 1994;Aufderheide and Rodríguez-Martín, 1998;Cook, 2002;Ortner, 2003;Cook andPowell, 2005, 2012), tuberculosis (lupus vulgaris) (Manchester, 1994;Ortner, 2003Ortner, , 2008aRoberts and Buikstra, 2003;Garg et al, 2010), and Wegener's granulomatosis (Chauhan and Cruz, 2007). It must be noted, however, that according to Manchester (1994: 80), in what concerns the interpretation of rhinomaxillary lesions only leprosy, tuberculosis (lupus vulgaris) and treponematosis "are of practical significance in paleopathological differential diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Myers et al [2] reported of nasal obstruction (34%), expansile mass (29.0%), epistaxis (23.0%) and epiphora (11.0%). Koivunen et al [11] also reported of nasal obstruction (25.0%), epistaxis (18.0%) and palpable tumor (12.0%) whereas Fasunla and Lasisi [8] reported of nasal obstruction and discharge (100%), cheek swelling (92.7%), cheek pain and paraesthesia (69.5%) and toothache (56.5%). This really indicates that patients who present with nasal blockage, epistaxis, nasal mass and others might be possible candidates of sinonasal tumors.…”
Section: Ent Updatesmentioning
confidence: 99%
“…[10] Koivunen et al reported nasal obstruction (35%), epistaxis (18%) and observable or palpable tumor (12%) in the cases studied. [11] Fasunla and Lasisi found epistaxis, obstruction and nasal discharge in all cases (100%), check swelling (92.7%), cheek pain and paraethesia (69.5%) and toothache (56.5%). [8] In another study by Waldron et al, the most common presenting symptoms were pain (59%), oral symptoms (40%), facial swelling (38%), nasal obstruction (35%) and epistaxis (25%).…”
mentioning
confidence: 99%